2022
DOI: 10.3390/ma15207308
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Graphene Nanoplatelets Dispersion and Its Performance in Cement Mortars

Abstract: As promising next-generation conducting materials, Graphene Nanoplatelets (GNPs) have been widely used to enhance the mechanical and pressure-sensitive properties of cement-based materials. However, this beneficial effect highly depended on its dispersion. In this study, polyvinyl pyrrolidone (PVP) surfactant, high-speed shear, and ultrasonication were used to disperse GNPs. To fully exert the mechanical and pressure-sensitive properties and enhance the dispersion effect of GNPs in cement-based materials, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Graphene has exceptionally high strength and stiffness, and when uniformly dispersed in concrete, it forms denser concrete structures, reducing the number and size of micro-defects in concrete. Researchers have found that the tensile and compressive performance of concrete can be improved by adding a moderate amount of graphene powder [ 39 ], single-layer graphene sheet powder [ 40 ], or graphene dispersion [ 41 ]. Additionally, the van der Waals forces between graphene and cement gel can reduce the distance between cement particles, facilitating complete hydration reactions and improving concrete’s overall strength [ 42 ].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Graphene has exceptionally high strength and stiffness, and when uniformly dispersed in concrete, it forms denser concrete structures, reducing the number and size of micro-defects in concrete. Researchers have found that the tensile and compressive performance of concrete can be improved by adding a moderate amount of graphene powder [ 39 ], single-layer graphene sheet powder [ 40 ], or graphene dispersion [ 41 ]. Additionally, the van der Waals forces between graphene and cement gel can reduce the distance between cement particles, facilitating complete hydration reactions and improving concrete’s overall strength [ 42 ].…”
Section: Mechanical Propertiesmentioning
confidence: 99%